Visitors to Guam modeling satisfaction, quality and intentions - Alampay, Ramon Benedicto A. (ProQuest Dissertations & Theses Global, 2003)
"Achieving customer satisfaction, it can be argued, is the core objective of marketing. However, in the tourism field, academics and managers often use the terms "satisfaction" and "perceived quality" interchangeably. While researchers generally agree that the two are related, they have not yet agreed on the nature of the causal relationship between them. Further, the research into how perceived destination quality and tourist satisfaction influence future purchase intentions remains limited. Given these issues, a study of the relationships between tourist satisfaction/dissatisfaction, perceived quality, and purchase intentions would contribute to greater understanding of the marketing concept as it applies to tourism. This study addresses the question of how tourists' post-visit evaluations (i.e. satisfaction and perceived quality) of their holiday experience influence their future intentions to return to or recommend a destination to others. Using survey data collected from 3,108 visitors to Guam between June 1998 to November 1999, a conceptual model relating visitor satisfaction (with individual components as well as with the destination as a whole), perceived quality of the destination, post-visit image and future intentions was developed and tested using structural equations modeling (SEM) techniques. The model hypothesized that satisfaction with the various components of a destination influenced evaluations of destination quality and overall satisfaction with the destination. Consequently, these evaluations help form an image of the place as a desirable vacation destination. This resulting image then influences tourists' future intentions regarding the place. Multiple structural equations models (MSEM) were run to test for differences in model fit between groups according to nationality, purpose of visit or previous visits to Guam. Tourists from Japan, South Korea, Taiwan and Hong Kong were interviewed to collect data for the analysis. By purpose of visit, the sample was divided into pleasure, corporate, and honeymoon groupings. Potential differences between first-time and repeat visitors were also assessed. The SEM analysis suggested that the original hypothesized model-where image fully mediated the effects of satisfaction and quality on intentions-could be improved by adding a direct path from overall satisfaction to behavioral intentions. This alternative model provided the better fit, indicating that post-visit image did not completely mediate the effects of satisfaction on intentions as had been originally hypothesized. The model also appeared to predict the probability of recommending the destination to others better than did the one based on future intentions to return to Guam. Finally, the MSEM indicated that the models for different groups-by nationality, purpose of visit or previous experience-differed significantly along various paths within the models."--Abstract.